At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Of course! Let’s solve the problem step-by-step:
### Step 1: Analyze the given quadratic equation
Given the quadratic equation:
[tex]\[ a^2 x^2 + 6 a b x + a c + 8 b^2 = 0 \][/tex]
For quadratic equations of the form [tex]\( Ax^2 + Bx + C = 0 \)[/tex] to have equal roots, the discriminant must be zero. The discriminant [tex]\( \Delta \)[/tex] is given by:
[tex]\[ \Delta = B^2 - 4AC \][/tex]
### Step 2: Identify coefficients
In our equation:
[tex]\[ a^2 x^2 + 6 a b x + a c + 8 b^2 = 0 \][/tex]
The coefficients are:
[tex]\[ A = a^2, \quad B = 6ab, \quad C = ac + 8b^2 \][/tex]
### Step 3: Compute the discriminant
The discriminant for our quadratic equation is:
[tex]\[ \Delta = B^2 - 4AC \][/tex]
Substituting the coefficients, we get:
[tex]\[ \Delta = (6ab)^2 - 4(a^2)(ac + 8b^2) \][/tex]
[tex]\[ \Delta = 36a^2b^2 - 4a^2(ac + 8b^2) \][/tex]
[tex]\[ \Delta = 36a^2b^2 - 4a^3c - 32a^2b^2 \][/tex]
[tex]\[ \Delta = 4a^2b^2 - 4a^3c \][/tex]
[tex]\[ \Delta = 4a^2(b^2 - ac) \][/tex]
For the roots to be equal, the discriminant must be zero:
[tex]\[ 4a^2(b^2 - ac) = 0 \][/tex]
Since [tex]\( a^2 \neq 0 \)[/tex], we can simplify this to:
[tex]\[ b^2 - ac = 0 \][/tex]
[tex]\[ b^2 = ac \][/tex]
### Step 4: Analyze the second equation
Given the second equation:
[tex]\[ ac(x+1)^2 = 4b^2 x \][/tex]
We want to show that this equation also has equal roots. Start by expanding and simplifying:
[tex]\[ ac(x^2 + 2x + 1) = 4b^2 x \][/tex]
[tex]\[ acx^2 + 2acx + ac = 4b^2x \][/tex]
Rearrange everything to one side:
[tex]\[ acx^2 + 2acx + ac - 4b^2x = 0 \][/tex]
[tex]\[ acx^2 + (2ac - 4b^2)x + ac = 0 \][/tex]
### Step 5: Compute the discriminant of the new equation
Identify the coefficients again:
[tex]\[ A' = ac, \quad B' = 2ac - 4b^2, \quad C' = ac \][/tex]
Compute the discriminant [tex]\( \Delta' \)[/tex]:
[tex]\[ \Delta' = (B')^2 - 4A'C' \][/tex]
[tex]\[ \Delta' = (2ac - 4b^2)^2 - 4(ac)(ac) \][/tex]
[tex]\[ \Delta' = (2ac - 4b^2)^2 - 4a^2c^2 \][/tex]
[tex]\[ \Delta' = 4( ac - 2b^2)^2 - 4a^2c^2 \][/tex]
[tex]\[ \Delta' = 4 \left( ac - 2b^2 \right)^2 - 4a^2c^2 \][/tex]
Since we know from earlier that [tex]\( b^2 = ac \)[/tex], substitute [tex]\( b^2 \)[/tex] back into the discriminant:
[tex]\[ \Delta' = 4 \left( ac - 2(ac) \right)^2 - 4a^2c^2 \][/tex]
[tex]\[ \Delta' = 4 \left( -ac \right)^2 - 4a^2c^2 \][/tex]
[tex]\[ \Delta' = 4a^2c^2 - 4a^2c^2 \][/tex]
[tex]\[ \Delta' = 0 \][/tex]
### Conclusion
The discriminant of the second equation is zero, indicating that it also has equal roots. So we have proven that if the equation [tex]\( a^2 x^2 + 6 a b x + a c + 8 b^2 = 0 \)[/tex] has equal roots, the equation [tex]\( a c(x+1)^2 = 4 b^2 x \)[/tex] also has equal roots.
### Step 1: Analyze the given quadratic equation
Given the quadratic equation:
[tex]\[ a^2 x^2 + 6 a b x + a c + 8 b^2 = 0 \][/tex]
For quadratic equations of the form [tex]\( Ax^2 + Bx + C = 0 \)[/tex] to have equal roots, the discriminant must be zero. The discriminant [tex]\( \Delta \)[/tex] is given by:
[tex]\[ \Delta = B^2 - 4AC \][/tex]
### Step 2: Identify coefficients
In our equation:
[tex]\[ a^2 x^2 + 6 a b x + a c + 8 b^2 = 0 \][/tex]
The coefficients are:
[tex]\[ A = a^2, \quad B = 6ab, \quad C = ac + 8b^2 \][/tex]
### Step 3: Compute the discriminant
The discriminant for our quadratic equation is:
[tex]\[ \Delta = B^2 - 4AC \][/tex]
Substituting the coefficients, we get:
[tex]\[ \Delta = (6ab)^2 - 4(a^2)(ac + 8b^2) \][/tex]
[tex]\[ \Delta = 36a^2b^2 - 4a^2(ac + 8b^2) \][/tex]
[tex]\[ \Delta = 36a^2b^2 - 4a^3c - 32a^2b^2 \][/tex]
[tex]\[ \Delta = 4a^2b^2 - 4a^3c \][/tex]
[tex]\[ \Delta = 4a^2(b^2 - ac) \][/tex]
For the roots to be equal, the discriminant must be zero:
[tex]\[ 4a^2(b^2 - ac) = 0 \][/tex]
Since [tex]\( a^2 \neq 0 \)[/tex], we can simplify this to:
[tex]\[ b^2 - ac = 0 \][/tex]
[tex]\[ b^2 = ac \][/tex]
### Step 4: Analyze the second equation
Given the second equation:
[tex]\[ ac(x+1)^2 = 4b^2 x \][/tex]
We want to show that this equation also has equal roots. Start by expanding and simplifying:
[tex]\[ ac(x^2 + 2x + 1) = 4b^2 x \][/tex]
[tex]\[ acx^2 + 2acx + ac = 4b^2x \][/tex]
Rearrange everything to one side:
[tex]\[ acx^2 + 2acx + ac - 4b^2x = 0 \][/tex]
[tex]\[ acx^2 + (2ac - 4b^2)x + ac = 0 \][/tex]
### Step 5: Compute the discriminant of the new equation
Identify the coefficients again:
[tex]\[ A' = ac, \quad B' = 2ac - 4b^2, \quad C' = ac \][/tex]
Compute the discriminant [tex]\( \Delta' \)[/tex]:
[tex]\[ \Delta' = (B')^2 - 4A'C' \][/tex]
[tex]\[ \Delta' = (2ac - 4b^2)^2 - 4(ac)(ac) \][/tex]
[tex]\[ \Delta' = (2ac - 4b^2)^2 - 4a^2c^2 \][/tex]
[tex]\[ \Delta' = 4( ac - 2b^2)^2 - 4a^2c^2 \][/tex]
[tex]\[ \Delta' = 4 \left( ac - 2b^2 \right)^2 - 4a^2c^2 \][/tex]
Since we know from earlier that [tex]\( b^2 = ac \)[/tex], substitute [tex]\( b^2 \)[/tex] back into the discriminant:
[tex]\[ \Delta' = 4 \left( ac - 2(ac) \right)^2 - 4a^2c^2 \][/tex]
[tex]\[ \Delta' = 4 \left( -ac \right)^2 - 4a^2c^2 \][/tex]
[tex]\[ \Delta' = 4a^2c^2 - 4a^2c^2 \][/tex]
[tex]\[ \Delta' = 0 \][/tex]
### Conclusion
The discriminant of the second equation is zero, indicating that it also has equal roots. So we have proven that if the equation [tex]\( a^2 x^2 + 6 a b x + a c + 8 b^2 = 0 \)[/tex] has equal roots, the equation [tex]\( a c(x+1)^2 = 4 b^2 x \)[/tex] also has equal roots.
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.